Magnetization Behavior of a Mixed Spin-3/2 and Spin-7/2 System on a Binary Square Lattice within the Blume-Capel Ising Model (Journal of the College of Basic Education, 2025)
This study investigates the magnetization behavior of a mixed spin-3/2 and spin-7/2 system arranged on a binary square lattice using the Blume- Capel Ising ferrimagnetic model within the framework of mean-field theory. The primary focus is on the influence of crystal fields on critical temperatures and magnetization curves. It is observed that varying the crystal field ratio DB/|J| yields a spectrum of magnetic behaviors, classified as types Q, R, and S. These results provide further insight into the phase transition characteristics of mixed-spin systems.